Identification and Registration of High Rhizome Essential Oil Yielding Variety of Curcuma zedoaria (Christm.) Roscoe (cv. Jor Lab CZ-6). Issue 5 (3rd September 2022) - Lal, Mohan; Baruah, Joyashree; Begum, Twahira; Darnei, Rose Laldinaii; Munda, Sunita; Paw, Manabi
Abstract: Curcuma zedoaria, commonly called 'white turmeric' is an aromatic rhizomatous herb of Zingiberaceae family. The root is used as an alternative to arrowroot and barley for producing 'shoti starch'. The leaves and rhizome essential oils are used in chemical, pharmaceutical and food industries for manufacturing various products. The present study aims at identifying essential oil rich variant of Curcuma zedoaria . Germplasm collection was done during the year 2016, followed by two-year initial varietal trial planted in replicated for selecting lines with high rhizome essential oil content during 2017 and 2018. The identified line "Jor Lab CZ-6" rich in essential oil yield (fresh weight basis, 0.69% w/w) was planted at four locations of North east India for stability analysis using Eberhart-Russell and Additive Main effect and Multiplicative Interaction model (AMMI) and was compared with two check varieties. Analysis of variance for stability study showed highly significant differences in the varieties for the traits studied at p<0.005. The traits viz., number of tillers per plant, fresh rhizome yield and rhizome essential oil yield were found stable for Jor Lab CZ-6 according to Eberhert and Russell model. Based on AMMI model, for rhizome essential oil yield and fresh rhizome yield per plant environment (E2 and E4) was found ideal with regards to stability and performance respectively. The agronomical and essential oil components traits studied were found higher in Jor Lab CZ-6 compared to the two check varieties. The essential oil subjected to Gas Chromatography/Mass Spectrometer profiling showed epicurzerenone as the major compound. With unavailability of high essential oil rich variant of C. zedoaria in public domain, this newly identified line can be a boon to the industries for commercial oil extraction purpose. The identified germplasm was registered with ICAR-National Bureau of Plant Genetic Resources, New Delhi.